Paul’s Transformation of Jesus’s Commands on Financial Support - Wenkel, David H. (The Evangelical quarterly, 2025)
This study offers a fresh reading of the apparently contradictory ways in which Paul handled Jesus’s commands regarding financial support for missionary workers. Paul’s crucifixion-shaped ethics meant that rights did not always have to be exercised. A synthetic and canonical survey considers how Paul handled matters differently in Corinth and Ephesus. This article demonstrates that Paul has transformed Jesus’s commands by integrating them into a wisdom hermeneutic that can be applied to various situations.